Examining the Type of Legal Representation and Its Influence on Disaggregated Dispositions in Juvenile Court - Brady, Caitlin M. (Youth violence and juvenile justice, 2021)
While prior studies of juvenile court outcomes have examined the impact of legal representation on out-of-home placement versus community sanctions, previous research has not fully explored the variation within sanctions that youth receive. The current study examines the influence of type of legal representation (public defender or private attorney) when predicting juvenile adjudications and dispositions. Using a sample of delinquent referrals from a Northeast state between 2009 and 2014, results showed that youth do receive different outcomes (e.g., probation, drug and alcohol treatment, accountability-oriented dispositions, etc.) based on the type of legal representation. The findings have important implications for juvenile court processing related to how courtroom actors impact case outcomes.